Accessibility of Primary Schools in Rural Areas and the Impact of Topography: A Case Study in Nanjiang County, China - Zhu, Yuanyuan; Zinda, John Aloysius; Liu, Qin; Wang, Yukuan; Fu, Bin; Li, Ming (Land (Basel), 2023)
In recent years, many developing countries have consolidated rural primary schools, closed small community schools, and enlarged centralized schools, which can reduce the accessibility of education to many communities. Meanwhile, expanding road networks may enable people in far-flung communities to access schools more easily. To evaluate the impacts of both trends on spatial justice in access to education, it is important to examine spatial patterns of primary school accessibility and their predictors. How do the topographic features of villages and surrounding landscapes correlate with primary school accessibility in rural upland areas? Using a digital map route planning application, this study evaluates the primary school accessibility of each village in Nanjiang County, a mountainous county in southwest China. By evaluating relationships between primary school accessibility and village characteristics, this study provides evidence corroborating frequent claims that rural remote mountainous areas have poor primary school accessibility. Additionally, by analyzing the effects of elevation and ruggedness of villages and of the zone between villages and schools as well as the mechanisms driving these effects, we find that, contrary to expectations, with increasing village elevation, a village’s primary school accessibility first decreases and then increases. The ruggedness of the terrain upon which a village is built has no significant effect. The ruggedness of the zone between a village and its nearest school exerts significant effects. These findings demonstrate that the two policies have created a pattern of spatial injustice that disadvantages peripheral villages, illustrating the need to attend to topography in efforts to provide equitable school access in rural mountainous areas.